2011
DOI: 10.1039/c1cc10268k
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic carbene containing element organic frameworks as heterogeneous organocatalysts

Abstract: A bifunctional imidazolium linker was used for the production of highly crosslinked element organic frameworks by Suzuki-coupling with tetrafunctional boronic acids. The resulting porous materials are good heterogeneous organocatalysts in the N-heterocyclic carbene-catalyzed conjugated umpolung of α,β-unsaturated cinnamaldehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 25 publications
2
59
0
Order By: Relevance
“…Figure 2 shows typical optical and electron micrographs of our nanoporous materials (see Supplementary Figs 32 and 33 for additional images). As evident from the electron micrographs, the structures of both PhotoPAFs and PhotoPAN lack long-range order, in agreement with previous reports 15,24,25 on PAFs obtained by irreversible C-C coupling reactions. Still, the porous nature of these materials can easily be discerned by transmission electron microscopy (TEM): focusing on the edge of the sample revealed the presence of B1 nm nanopores (Fig.…”
Section: Synthesis Of Nanoporous Materials Incorporating Spiropyransupporting
confidence: 79%
“…Figure 2 shows typical optical and electron micrographs of our nanoporous materials (see Supplementary Figs 32 and 33 for additional images). As evident from the electron micrographs, the structures of both PhotoPAFs and PhotoPAN lack long-range order, in agreement with previous reports 15,24,25 on PAFs obtained by irreversible C-C coupling reactions. Still, the porous nature of these materials can easily be discerned by transmission electron microscopy (TEM): focusing on the edge of the sample revealed the presence of B1 nm nanopores (Fig.…”
Section: Synthesis Of Nanoporous Materials Incorporating Spiropyransupporting
confidence: 79%
“…Not surprisingly, imidazolium ions have been also frequently introduced into microporous polymers. 199,202,203 Recently Coskun et al reported a series of cationic microporous networks based on bipyridinium salts as monomers which were reacted into a porous polymer by a Sonogashira-Hagihara crosscoupling reaction with tetrakis(4-ethynylphenyl)methane. 204 The porous cationic polymers exhibited a high affinity towards CO 2 with isosteric heats of adsorption between 28.5 and 31.6 kJ mol À1 a n dg o o dC O 2 /N 2 selectivity.…”
Section: Cationic Microporous Polymersmentioning
confidence: 99%
“…21 A large variety of functional groups and polymerization schemes have been described to enable the synthesis of such extended polymer networks with high permanent porosity. [21][22][23][24][25][26][27][28][29][30] Functionalized tetraphenylmethanes have been frequently used as tectons, yielding porous polymer networks with sometimes exceptionally high surface areas 19,31,32 For example, the reaction of tetrakis(4-aminophenyl)methane with terephthaldehyde resulted in the formation of a three-dimensional polyimine network with permanent microporosity. Noteworthy, even a periodic covalent organic framework is formed from this approach.…”
Section: N-heterocyclic Carbenes (Nhcs)mentioning
confidence: 99%
“…17 Recent studies showed that functionalized NHCs can also be applied as maintaining part of metal organic frameworks (MOFs) 18 or in polymer networks with intrinsic microporosity (PIMs). 19,20 The latter materials are prepared from rigid and contorted molecules, oen called knots or tectons which are polymerized either directly or using linear linkers. 21 A large variety of functional groups and polymerization schemes have been described to enable the synthesis of such extended polymer networks with high permanent porosity.…”
Section: N-heterocyclic Carbenes (Nhcs)mentioning
confidence: 99%